Thermal Storage for the Analysis of Hybrid Energy Systems Based on Geothermal and Solar Power. (18th May 2022) - Aravind, K. U.; Mekala, N. Muthu; Muthuraju, N. P.; Soni, N. B.; Al-Ammar, Essam A.; Seikh, A. H.; Siddique, M. H.; Christopher, David
Abstract : Thermal degradation of geothermal energy occurs even during the duration of geothermal energy facilities. The enormity and efficiency of thermal energy available for electric transformation, as well as plant performance and power production, are both affected by the decrease in geofluid heat. Additionally, due to the generally increased turbine exhaust temperatures, the efficiency of geothermal energy based upon air-cooled organic Rankine cycle devices (ORCs) degrades considerably at hot room temperatures. A newly designed Geothermal-Concentrator Solar Power (GEO-CSP) station is simulated in this work, which allows for greater geothermal power use and enhances the effectiveness of the geothermal ORC system over the power plant's lifespan. The geothermal fluid entering the ORC's heating element is heated using the sun's radiation. The CSP facility is fitted with a thermal energy storing unit that stores excess energy from the sun accessible throughout the day and releases it at nighttime whenever the energy system's performance is better. When the storage facility is included in the concentrator CSP technology, the incremental yearly energy generation from solar increases by 19 percent, from 5.3 percent to 6.3 percent, similar to the geothermal-only plant. As a result, adding a TES unit to the hybrid unit could be quite beneficial.